The witch's dog at the school of spells - Rodgers, Frank, 1944- (London : Puffin, 1998)
A young English boy describes his relationship with his father and the special adventure they share together.
Keywords: Charms -- Juvenile fiction; Witches -- Juvenile fiction; Magic -- Juvenile fiction